(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
This paper investigates the pedagogical effectiveness of combining the Lexical Approach with Content and Language Integrated Learning (CLIL) in the context of English for Specific Purposes (ESP). Technical content and linguistic form are frequently at odds in traditional ESP training. This study suggests that the best linguistic engine for the content-driven CLIL framework is the Lexical Approach, which focuses on multi-word units and collocations. The research shows that this integrated approach dramatically lowers cognitive load, speeds up the acquisition of professional discourse, and increases learner motivation through a mixed-methods longitudinal study of engineering students. Results indicate a 25% increase in technical fluency and a marked improvement in the naturalness of academic writing.